Implementation of Project Based Learning Model to Develop Students' Creativity and Collaboration Skills in P5 - Rita Yuliyanti; Sintia Febriyanti; Agung Setyawan (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the implementation of Project-Based Learning (PjBL) as an innovative approach centered on real-world projects, in line with the Pancasila Student Profile Strengthening Project (P5) under the Merdeka Curriculum, to improve students' independence, creativity, problem-solving skills, and internalize Pancasila values ​​such as mutual cooperation, creativity, and environmental responsibility through project examples such as "School Environmental Cleanliness Movement" and "Changing Waste into Valuable Items"; the research method is descriptive-analytical with systematic stages including pre-project planning, observation, prototype development, evaluation and revision, completion and launch, and post-project assessment, emphasizing student autonomy, full responsibility, multi-stakeholder engagement, creative thinking, and a tolerant classroom atmosphere; research results indicate that PjBL creates a holistic learning environment with advantages such as fostering critical thinking, skill development, active participation, teaching flexibility, and collaborative capabilities, despite facing challenges such as high costs, long timeframes, substantial equipment requirements, student inactivity within groups, and uneven topic mastery. It is hoped that it will foster a generation of intelligent, principled, and globally ready students through meaningful and engaging education.